Cell Death Induction by the Indirubin Derivative 7BIO and the BH3 Mimetic Drugs ABT-737 and GX15-070 in Medullary Thyroid Carcinoma Cells - Broecker-Preuss, M.; Becher-Boveleth, N.; Mann, K. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Purpose: Patients with advanced and metastasized medullary thyroid carcinoma are difficult to treat since tumor cells do not respond to chemotherapeutic treatment and external radiation. Direct induction of cell death is a new therapeutic approach to therapy-resistant tumor cells. In this study we analyzed the effect of the indirubin-derivative 7BIO and the BH3 mimetic drugs ABT-737 and GX15-070 on cell death induction of TT medullary thyroid carcinoma cells.Methods: TT medullary thyroid carcinoma cell line was treated with 7BIO, ABT-737 and GX15-070. Cell viability was analyzed by MTT assay, while cell death was determined by caspase 3/7 activity, measurement of caspase cleavage products and lactate dehydrogenase liberation assay. LC3B cleavage was analyzed by western blot.Results: Incubation with all 3 drugs efficiently decreased the number of viable TT cells with IC50 values of 4.1 µM (7BIO), 0.19 µM (ABT-737) and 0.23 µM (GX15-070). The BH3 mimetic ABT-737 caused an apoptotic cell death with caspase activation as expected, while 7BIO- and GX15-070-treatment led to a mixed kind of cell death, where caspase activation was detected but had no effect on viability of TT cells. LC3 conversion as a biochemical marker of autophagic cell death was observed after GX15-070 treatment while LDH release pointed to involvement of necrosis after treatment with all 3 drugs.Conclusion: The BH3 mimetic drugs ABT-737 and GX15-070 efficiently killed TT medullary thyroid carcinoma cells with low IC50 values, while the indirubin-derivative 7BIO was also effective but with a higher IC50 value. Although the exact kind of cell death and target molecules of 7BIO and GX15-070 are not yet defined, direct induction of cell death may be a new therapeutic option in medullary thyroid carcinoma cells.
Keywords: BCL-2 inhibitor; medullary thyroid cancer; apoptosis